Antioxidant effect of essential oils on RTC pork chops and its evaluation by Raman spectroscopy. Issue 5 (27th February 2018) - Zhang, Huiyun; He, Peng; Li, Xinling; Kang, Huaibin
Abstract: The antioxidant effects of clove and cinnamon essential oils (EOs) on retarding lipid and protein oxidation was investigated in ready‐to‐cook (RTC) pork chops during refrigerated storage at 4 ± 1 °C. The samples were coated with 0.2% (v/w) clove and cinnamon EOs and then stored for 13 days. The treated samples and the control were analysed periodically for lipid and protein oxidation by chemical detection, Raman spectroscopy, and sensory evaluation. Coating the samples with clove and cinnamon EOs efficiently retarded lipid and protein oxidation in all the RTC pork chops during refrigerated storage. It was found that clove essential oil has higher antioxidant activity than cinnamon essential oil in pork chops. Raman spectroscopy analysis revealed a decrease ( p < .05) in area of the band at 1, 448 cm −1, accompanied by an increase ( p < .05) in storage time. In addition, Raman spectra demonstrated a higher sensitivity for antioxidant evaluation than 2‐thiobarbituric reactive substances. Sensory evaluation revealed that coating RTC pork chops with EOs extended the shelf life of refrigerated storage by at least 3 days. These results indicated that both clove and cinnamon EOs are effective in retarding lipid and protein oxidation in RTC pork chops. Practical application: Antioxidant effect of clove and cinnamon essential oils on RTC pork chops was observed. Oxidation of RTC pork chops during chilled storage was monitored by chemical detection and Raman spectroscopy. Raman spectroscopy results and TBARS values provided compatible information. Shelf life of RTC pork chops was increased 3 days with the EO treatment.